The Floating Market of Lok Baitan, South Kalimantan - Ellyn Normelani (Program Pascasarjana, 2016)
Tourism plays an important role in the development of local economic. Tourism has been reported contributes significantly in the local development. Floating market in South Kalimantan has potentiality as tourism attraction, but there are limited study of the value of floating market as tourism attraction. This paper aims to describe the floating market in Lok Baitan, South Kalimantan as a potential attraction for local tourism development. This paper confirm that principally floating market is the integral part of the local people in South Kalimantan, especially who live along Barito rivers. Floating market rich in term of natural and cultural resources that is potential to further development as tourism attractions. There are also numerous possibility to develop tourism programs, ranging from nature based tourism to cultural tourism. In the perspective of tourism development, the community based tourism see to be the significant strategy to develop. Through community based tourism, floating market tourism in Lok Baitan will contribute to the local economi development. From such resources, there are numerous possibility for the development of tourism program and attractions. In such a case, floating market tourism in Lok Baitan should be set up following community based tourism. This will become the key for tourism as a component and strategy for local economic development. Keywords: community based tourism development, culture preservation, floating market, South Kalimantan.